Characterization of Green Infrastructure at the Local Level with Geographical Information System, Tunja (Colombia) - Hernández-Rojas, Cristian Camilo; Sanabria-Marín, Rigaud (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article presents a characterization of the areas likely to integrate a Green Infrastructure (GI) for the Tunja city at local scale and spatial analysis is mainly applied to the land cover and land use of the study area. To identify the areas that could be integrated into the GI, four thematic dimensions were first zoned (ecological connectivity, multifunctionality, ecological status and accessibility to the population); they were later normalized on a scale of 1 to 10 to make them comparable; the dimensions were combined by an Analytic Hierarchy Process (AHP) and finally those areas whose pixel values ​​were above the third quartile were selected in the integration of the dimensions. The zoned dimensions the following weights were obtained: ecological connectivity (48%), multifunctionality (30%), ecological status (13%) and accessibility to the population (9%). It was found that the main areas likely to integrate into the GI are concentrated in the western fringe of the city; however, the northwestern area has a greater fragmentation and lower ecological status than the southwestern zone (which refers mainly to the Protective Forest Reserve El Malmo). Likewise, several areas or patches were identified to the south of the city (referring mainly to wooded areas and presence of wetlands) as well as small wooded areas in the urban perimeter, but with greater isolation among the other areas of GI. Within the urban perimeter the zoning of areas that could be integrated into a GI was practically null.